TINGKAT PENGGUNAAN Azolla pinnata PADA PAKAN TERHADAP PERTUMBUHAN IKAN NILA (Oreochromis niloticus) Grade of use of azolla pinnata the feed to growth of nila fish (Oreochromis niloticus) - Daniel Sinaga; Syammaun Usman; Nurmatias Nurmatias (AQUACOASTMARINE, 2016)
Nila fish is economic valuable fish, consumer demand increasing, but hasnot been followed by intensive cultivation and optimal. One of attempt toovercome these problems by substituting commercial feed with fish meat mealAzolla pinnata for growth nila fish. The tested fish are nila fish size 6 cm whichmaintained in an pain diameter 50 cm by 12 unit. With completely randomizeddesign. With treatment commercial pakan 100% without added azolla flour,commercial pakan 94 % added 10 % azolla flour, commercial pakan 88 %added 20 % azolla flour, and commercial pakan 82 % added 30 % azolla flour,the result showed that azolla flour can be used as a substitute for fish meal in fishfeed. The fourth feed that gives the best growth as feeds commercial pakan 82 %added 30 % azolla flour with weight growth of 4.33 g and length growth 2.23 cm.Keywords : Oreochromis niloticus, Azolla pinnata flour, Growth